Classic Charles Dickens 2 - Copperfield, David (New Delhi : Penguin Books, 2012)
His superb eye for detail has conjured some of the most memorable characters in English fiction from the cruel Miss Havisham of Great Expectations to the treacherous Uriah Heep of David Copperfield. This timeless collection brings together his most iconic novels.
Keywords: Classic -- fiction